Host Factor Interaction Networks Identified by Integrative Bioinformatics Analysis Reveals Therapeutic Implications in COPD Patients With COVID-19 - Zheng, Wenjiang; Wang, Ting; Wu, Peng; Yan, Qian; Liu, Chengxin; Wu, Hui; Zhan, Shaofeng; Liu, Xiaohong; Jiang, Yong; Zhuang, Hongfa (Frontiers in Pharmacology, 2021)
Background: The COVID-19 pandemic poses an imminent threat to humanity, especially for those who have comorbidities. Evidence of COVID-19 and COPD comorbidities is accumulating. However, data revealing the molecular mechanism of COVID-19 and COPD comorbid diseases is limited. Methods: We screened the top 500 genes of COVID-19 and COPD and then selected some data from the Host genes database (FDR<0.05, |LogFC|≥1) to supplement. Ultimately, 492 co-morbid host factors of COVID-19 and COPD were obtained. Results: We revealed the comorbidity mechanism of COVID-19 and COPD from the perspective of host factor interaction, obtained the top ten gene and 15 modules with different biological functions. Furthermore, we have obtained the top 30 signaling pathways and concluded that dexamethasone shows effective interventions. Conclusions: This study revealed host factor interaction networks for COVID-19 and COPD, which could confirm the potential drugs for treating the comorbidity, ultimately, enhancing the management of the respiratory disease.